Meningkatkan Hasil Belajar Matematika dengan Model Pembelajaran Arias Menggunakan Media Kartu Positif dan Negatif - Sariyanti, Eka (Journal of Edukasi Borneo, 2024)
The problem in this study was the low mathematics learning outcomes of students. This study aimed to determine the improvement in mathematics learning outcomes of students after the implementation of the ARIAS learning model in mathematics subjects for junior high school students (SMP) in Jelimpo, Landak Regency. This study was classroom action research (PTK) which is carried out in two cycles. This study involved 33 students of grade VII. Data were collected from test and observation. Test techniques were used to measure student learning outcomes. Observation data were used to identify the implementation of the ARIAS model in mathematics learning. The student learning outcome data were analyzed using descriptive statistics. The results of this study indicate that the application of the ARIAS learning model can improve students' mathematics learning outcomes. This can be seen in the improvement of the learning outcomes in cycle I of student completeness by 45.45%, and completeness in cycle II of 78.78%. Based on the results of this study, it can be concluded that the use of the ARIAS learning model had a positive effect on students' mathematics learning outcomes of the students.   ABSTRAK Permasalahan dalam penelitian ini adalah rendahnya hasil belajar matematika siswa. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar matematika siswa setelah diterapkannya model pembelajaran ARIAS pada mata pelajaran matematika pada siswa sekolah menengah pertama (SMP) di Jelimpo, Kabupaten Landak. penelitian ini adalah penelitian tindakan kelas (PTK) yang dilaksanakan dengan dua siklus. penelitian ini melibatkan 33 siswa kelas VII. Pengumpulan data hasil belajar menggunakan teknik tes dan observasi. Teknik tes digunakan untuk mengukur hasil belajar siswa. Data observasi digunakan untuk mengidentifikasi implementasi model ARIAS dalam pembelajaran matematika. Data hasil belajar siswa dianalisis secara statistik deskriptif. Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran ARIAS dapat meningkatkan hasil belajar matematika siswa. Hal ini dapat terlihat pada peningkatan hasil belajar pada siklus I ketuntasan siswa sebesar 45,45%, dan ketuntasan pada siklus II sebesar 78,78%. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penggunaan model pembelajaran ARIAS berpengaruh positif terhadap hasil belajar matematika siswa pada siswa kelas VII SMP. KATA KUNCI: Hasil belajar, matematika, penerapan model pembelajaran ARIAS, kartu positif dan negatif.